Minimizing Negative Distributional Effects of Public Sector Downsizing - Razzaz, Susan (World Bank, Washington, DC, 2012)
Downsizing programs are an important part of many public sector reforms supported by the World Bank. Although these programs can reduce budget deficits and address inefficiencies caused by state-led development strategies, many observers are concerned about the political and social consequences of mass layoffs as well as the disproportionate share of the losses that some groups of workers may bear. This note examines the differing possible impacts of downsizing on male and female employees and the consequences for households and the economy at large. After discussing why the distributional consequences of downsizing are important, the note introduces a simple tool that can be used in the design of downsizing programs to minimize negative distributional consequences. Although this note focuses on the differing effects of downsizing on men and women, similar concerns apply to other categories of workers (such as different ethnic groups). This tool can easily be adapted to minimize the negative distributional consequences for other groups as well.